Genetic Testing and its Role in Precision Medicine: Understand Disease Risk and Tailoring Treatments - Islam, Zahoor; Zainullah; khan, Adil; Aslam , Minahal; Khan, Asad Ullah; Maqsood ur Rehman (Indus Journal of Bioscience Research, 2025)
This paper presents a systematic review exploring the role of genetic testing in precision medicine, focusing on its ability to predict disease risk, personalize treatment strategies, and enhance clinical decision-making. Genetic testing offers significant potential in early disease detection, particularly for conditions with strong genetic components such as cancer, cardiovascular diseases, and neurodegenerative disorders. By identifying high-risk individuals, genetic tests enable proactive interventions that can improve health outcomes and reduce disease burden. Additionally, genetic testing plays a crucial role in tailoring treatments, especially in oncology and pharmacogenomics, by providing insights into how patients will respond to specific drugs, leading to more effective and safer therapies. However, challenges remain in integrating genetic testing into routine clinical practice due to barriers like cost, accessibility, and the complexity of genetic data interpretation. Ethical concerns, insurance coverage issues, and the need for better clinician training also hinder its widespread adoption. Despite these challenges, genetic testing holds transformative potential, and with advancements in technology, policy, and education, it is poised to revolutionize healthcare by enabling more personalized, effective, and efficient care. This paper provides a comprehensive understanding of the current landscape and future directions for genetic testing in precision medicine.